Relationship Between the Incidence of Rampant Caries and Parents' Knowledge Level on Oral Hygiene Patterns in Toddlers - Parmasari, Wahyuni Dyah; Cahyani, Nafansya Regita; Suryawati, Sianny; Erny, Erny (Dentistry Faculty, 2024)
Background: Rampant caries is a common oral health problem in toddlers. Risk factors for rampant caries in toddlers are multifactorial, including important behavioral factors, such as poor oral hygiene patterns, patterns of bottle feeding more than three times a day and often given at bedtime, lack of use of flour in toothpaste, and improper tooth brushing. This can increase the risk of caries in toddlers. Parents' knowledge about how to clean the oral cavity properly can help reduce the risk of caries rampant in toddlers. Purpose: The purpose of the study was to determine the relationship between the incidence of caries rampant and the level of knowledge of parents of toddlers on oral cleaning patterns. Method: The study used analytic observations with a cross-sectional approach. The study population was 59 toddlers in Posyandu Kenanga 2, and the sample size was 30 toddlers the sampling technique used was purposive sampling. Analysis of research data using the Chi-square test. Result: The results showed that toddlers in Posyandu Kenanga 2 Gadingmangu Perak Jombang experienced Dental caries rampant (81.3%) with a poor level of parental knowledge (60.0%) and caries rampant (18.8%) with a good level of parental knowledge (40.0%). Conclusion: This study concludes that there is a relationship between the incidence of caries rampant and the level of knowledge of parents of toddlers on oral cavity cleaning patterns, p-value = 0.011 ( 0.05).